A systematic review and meta-analysis on surgical treatment for painful neuromas - Luis Rafael Moscote-Salazar; William Andrés Florez-Perdomo; Juan Sebastián Reyes Bello; Claudia Marcela Restrepo Lugo; Amgad Hanna (World Neurosurgery: X)
Objective: With the increasing advances in therapeutic approaches for painful neuromas in upper and lower limbs, this study aims to comprehensively assess surgical interventions by evaluating their effectiveness, techniques, and outcomes. Methods: The authors conducted a systematic review and meta-analysis following guidelines such as the MOOSE declaration for systematic reviews and the Cochrane Manual of Systematic Reviews and Meta-Analyses. The search was performed in several databases, and inclusion criteria enclosed randomized controlled trials (RCTs), observational studies, and case reports that examined other surgical techniques for managing painful neuromas. Quality assessment was carried out using appropriate scales for different study types. Results: A total of 612 patients from 25 studies (3 RCTs, 9 observational retrospective cohorts, and 13 case series) with painful neuromas in the upper and lower limbs were included in the analysis. Preoperative pain levels were significantly reduced post-surgery, as indicated by mean preoperative scores on the Visual Analog Scale (VAS) of 8.4 (SE 0.117, p < 0.00000001) for upper extremity neuromas and 8.38 (SE 0.158, p < 0.00001) for lower extremity neuromas. Following surgical interventions, pain scores decreased to 3.05 (SE 0.335, p < 0.00000001) and 3.49 (SE 0.263, p < 0.00001) on the VAS for upper and lower extremity cases, respectively. Conclusions: Despite the diversity of surgical techniques employed, significant pain reduction was consistently observed, indicating the potential benefits of these approaches. This systematic review and meta-analysis contribute valuable insights to the field, emphasizing the need for further research to optimize the management of painful neuromas.